Ammonia as Promising Fuel for Solid Oxide Fuel Cells: Experimental Analysis and Performance Evaluation. (10th July 2019) - Stoeckl, Bernhard; Preininger, Michael; Subotić, Vanja; Schroettner, Hartmuth; Sommersacher, Peter; Seidl, Michael; Megel, Stefan; Hochenauer, Christoph
Abstract : In the course of this study the direct utilization of ammonia in different types of solid oxide fuel cells (SOFCs), such as anode- and electrolyte-supported SOFC, is investigated. Experiments in low fuel utilization, exhibited excellent performance of ammonia in SOFCs, although the power outputs of equivalent hydrogen/nitrogen fuels were not attained due to the incomplete endothermic ammonia decomposition. Next, the single cells were operated under high fuel utilization conditions and methane was added to the humidified ammonia stream, where they showed excellent ammonia- and methane conversions. The stability of the cells used was proven over a period of at least 48 hours with a variety of fuel mixtures. Post mortem scanning electron microscopy analysis of the anode micro-structures indicated nitriding effects of nickel, as microscopic pores and enlargements of the metallic parts occurred. Finally, a long-term test over 1, 000 hours was carried out using a ten-layer stack consisting of electrolyte-supported cells.